THE ROLE OF COMMUNICATION MANAGEMENT IN THE PROCESS OF FORMATION AND DEVELOPMENT OF THE ORGANIZATIONAL CULTURE OF THE ENTERPRISE - BAHAN, Nadiia; SOBCHYSHYN, Vitaliy; DIACHENKO, Viktoriia; VLASENKO, Lidiya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the influence of communications on the process of formation and development of the organizational culture of the enterprise. Information and communication are the main element of interaction of all links of the social environment and play an important role in the process of effective management and formation of organizational culture at the enterprise. A detailed analysis of the classification of communications was carried out. It has been proven that the communication process is an important element for the effective functioning of the enterprise as a complex object of management, which is based on human relations. Effective information exchange is a key component of all major types of management activities, therefore communication acts as an integrated process, and incompleteness or interruption of communication processes can significantly reduce the effectiveness of management and cause negative consequences. The development of an effective system of internal communication at the enterprise, which helps to improve the coordination of actions, prompt decision-making and reduce the number of errors, is studied, which is important not only for individual enterprises, but also for the development of the national economy as a whole. It is substantiated that communications at the enterprise play a key role in the process of formation and development of organizational culture, they influence how employees interact, exchange information and jointly solve problems. Organizational culture acts as a powerful means of influencing the working atmosphere, staff motivation and the overall success of the enterprise. Generalized aspects of the influence of communications on the organizational culture of the enterprise, thanks to which it becomes clear that communications are a fundamental tool for building and maintaining organizational culture, as they ensure constant exchange of information, mutual understanding and unity in achieving common goals.